Trace of Philosophy and Religion Taoism in Najasataichi Shrine of Chon Buri Province - Lan, Changlong (Academic and Research Journal of Liberal Arts (Online), 2018)
The purpose of this study was to review the views of Chinese scholars on Philosophy and Religion Taoism. It especially aimed to study the historical events of Philosophy and Religion Taoism. Also, this study attempted to study the trace of Chinese philosophy and religion in the art of Najasataichi Shrine.The researcher used the qualitative research methodology to study the related documents and data from fieldwork; then analyzed the research purpose according to the document data, and put forward the research result by descriptive analysis. The results of the study are as follows: 1) most Chinese scholars agree that Philosophy Taoism is a philosophical school in China while Religion Taoism is a religious school originating from Chinese primitive natural belie, 2) important historical events connected with Purposive Taoism happened in the early Western Han Dynasty. The emperors managed state affairs under the guidance of the Taoist belieft, and thus led it into its glory days. Since Emperor Wu gave his order of respecting only Confucianism, however, Philosophy Taoism began to fall into low tide period, 3) important historical events connected with Religion Taoism are the reforms the Taoists carried out from the Jin Dynasty to the Northern and Southern Dynasties. The impetus for them to have a reform perhaps is related to Buddhism, because many Buddhists began to translate a great amount of Buddhist classics with the support of the hierarchy during this period. That’s why the number of Buddhists at that time was naturally greater than those of other religion followers, and 4) the philosophical and religious beliefs that the Chinese arts in Najasataichi Shrine contains originated mainly from Religion Taoism, Buddhism and Confucianism.